TRANSLATORSâ€™ CENSORSHIP IN ENGLISH-INDONESIAN TRANSLATION OF DONALD DUCK COMICS - Yuliasri, Issy (Universitas Pendidikan Indonesia, 2017)
Not all aspects of Western culture, reflected in the language used in Walt Disneyâ€™s Donald Duck comics, are acceptable in Indonesia. So, in translating the comics, the translators have to manipulate the text for it to be acceptable by the target readers and parents. This research aims at finding out censorship through the translation techniques used by the translators in translating the English humorous texts in the Walt Disneyâ€™s Donald Duck comics into Indonesian and the reasons underlying the translatorsâ€™ choice of the translation techniques. It also aims at analysing whether or not the choice of the translation techniques affects the rendering of meaning, maintenance of humour, and acceptability of the translation. For these purposes a qualitative method was employed with content analysis technique and reader response analysis. Content analysis was used in comparing the source text (ST) and target text (TT) to find out the translation techniques used as a means of censorship and to find out the translatorsâ€™ reasons for choosing the techniques. Reader-response analysis was done to find out the readersâ€™ response to the rendering of meaning and maintenance of humour in the translation. The research findings discovered that the translators performed censorship through the dominant use of reduction and generalisation techniques so as to reduce sarcasm and insults. The interview with the publisherâ€™s Senior Editor also revealed that â€œdecencyâ€ was the first priority in the translation decision making, followed by clarity of meaning and maintenance of humour.Â Further research to investigate other elements censored, and compared with other translated comics is recommended.